Misconception in Differentiated Learning Practices: A Study of Indonesian Social Studies Teachers - Syaharuddin Syaharuddin; Herry Porda Nugroho Putro; Muhaimin Muhaimin; Jumriani Jumriani; Sigit Triyono; Zain Ahmad Fauzi; Helmi Akmal; Mutiani Mutiani; Tarquam McKenna (International Journal of Social Learning (IJSL), 2025)
Differentiated learning can foster creativity, independence, and motivation to learn in students. However, misconceptions in understanding and implementing this approach produce negative outcomes. This study analyzes misconceptions in differentiated learning among Indonesian social studies teachers, examining their forms, causes, and impacts. A qualitative descriptive method was employed, utilizing structured and open-ended interviews conducted via Google Forms, with 126 randomly selected social studies teachers across Indonesia. Data were analyzed using the Miles and Huberman model. Results reveal significant misconceptions among Indonesian social studies teachers. Key findings include an overemphasis on learning styles (auditory, visual, kinesthetic) in teaching practices, uniform time allocation despite varying student abilities, and excessive reliance on group learning without considering individual student profiles, including those who prefer independent learning. These misconceptions reveal fundamental misunderstandings about the principles of differentiated instruction, underscoring the need for enhanced teacher training and professional development programs.